Gambling motivation among tourists in Macau's casino resorts. Issue 11 (1st November 2016) - Ma, Erdan; Lai, Ivan Ka Wai
ABSTRACT: The number of tourists visiting casino resorts has risen in recent years. Tourists often view gambling as a leisure activity option that they can participate in during their holiday. This study aims to investigate the motives that influence tourists' gambling intention. A list of potential motives is derived from the extensive tourism literature, and a sample including 462 respondents was collected in Macau. The survey results indicate that benefits, learning, pleasure, costing, and socialization are all motives for tourists to engage in recreational gambling. However, adventure, relaxation, prestige, and winning are not influencing factors among tourists who gamble during their trip. The study also explores the moderating roles of gender, age, and educational level on the relationship between different motives and gambling intention. Understanding the motives for why tourists gamble is useful for integrated resort operators to formulate marketing strategies for attracting tourists.